Presidential Decree-Law No. 98 of the Year 2015 Amending Some Provisions of the Law Concerning Supervision and Control on Insurance in Egypt, As Promulgated by Law No. 10 of the Year 1981 = قرار رئيس جمهورية مصر العربية بالقانون رقم 98 لسنة 2015 بتعديل بعض أحكام قانون الإشراف والرقابة على التأمين فى مصر الصادر بالقانون رقم 10 لسنة 1981 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic